Iron Status in Malnourished Children : A Cross Sectional Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Objectives: Malnutrition is a common condition among children and iron status varies in different types of malnutrition. So the present study is aimed to find the different iron status among severe malnourished children in our context. Methods: A hospital based cross sectional study was done in the Paediatrics ward Chittagong Medical College Hospital in a period of 6 months from January to July 2013 among the 50 cases of malnourished children of age range between 1 to 5 years and Weight for Height Z score(WHZ) was